Coral disease in the Indian Ocean: taxonomic susceptibility, spatial distribution and the role ofhost density on the prevalence of white syndrome - Hobbs, Jean-Paul; Frisch, A. (Inter-Research, 2010)
Coral diseases, such as white diseases and white syndrome (WS), have caused widespreaddamage to coral reefs throughout the Caribbean and are increasing in prevalence on PacificOcean reefs. The current study confirms that WS is also present on coral reefs in the Indian Ocean and tests whether patterns in taxonomic susceptibility and spatial variability conform to patterns of WS reported in the Pacific Ocean. Underwater surveys at 19 sites around Christmas and Cocos Islands revealed that WS primarily affects Acropora plate corals (A. clathrata, A. cytherea and A. hyacinthus), and prevalence of WS varied significantly across all 3 spatial scales investigated (island, exposure and depth). Approximately 13.0% (range = 0 to 43% per site) of plate corals at Christmas Island sites exhibited WS compared to <1% at the Cocos Islands. At Christmas Island, WS prevalence was greater in shallow (31.5%) than in deeper water (6.7%) and greatest on the northern (leeward) side of the island (31.5%) compared to the more exposed coastlines (0 to 1.5%). Importantly, the spatial distribution of WS was positively correlated with host density, but not with hard coral cover, suggesting a role of host density in WS outbreaks. Overall the present study has established that WS is impacting remote, near-pristine reefs in the Indian Ocean. However, the highly variable spatial distribution of WS illustrates that patterns in disease prevalence, and the subsequent impact on coral reefs, can be location- or region-specific.